2011
DOI: 10.3109/0886022x.2011.559299
|View full text |Cite
|
Sign up to set email alerts
|

BMI, spKt/V, and SBP but Not DBP Are Related to LVH in Chinese Maintenance Hemodialysis Patients

Abstract: Objective: Left ventricular hypertrophy (LVH) is the strongest predictor of cardiovascular mortality, the leading cause of death in hemodialysis (HD) patients. This study aims to identify the potential risk factors for LVH in HD patients. Methods: Exactly, 164 patients (84 men and 80 women) who had been on HD treatment for at least 6 months were enrolled. Clinical data were collected. Anthropometric measurements, biochemical analyses, and echocardiography were performed. The risk factors were determined by mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
2
4
1
Order By: Relevance
“…As depicted in Table 1 , SBP was significantly greater in hypertensive patients with baseline ECG LVH, which was consistent with a previously reported study by Cao et al [ 20 ] Therefore, ECG LVH could be considered an early indicator of poor BP management. After adjusting for multiplicity, the current study indicated that hypertensive patients with baseline ECG LVH exhibited a higher rate of unsatisfactory BP control (Table 2 ) and significantly smaller changes in SBP and DBP (Table 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…As depicted in Table 1 , SBP was significantly greater in hypertensive patients with baseline ECG LVH, which was consistent with a previously reported study by Cao et al [ 20 ] Therefore, ECG LVH could be considered an early indicator of poor BP management. After adjusting for multiplicity, the current study indicated that hypertensive patients with baseline ECG LVH exhibited a higher rate of unsatisfactory BP control (Table 2 ) and significantly smaller changes in SBP and DBP (Table 2 ).…”
Section: Discussionsupporting
confidence: 91%
“…Severity of anaemia could very well predict the left ventricular dimension and thickness in both male as well as female patients, and therefore risk of CVDs. 10,11…”
Section: Male Femlae 63mentioning
confidence: 99%
“…And low-dose dialysis may increase the accumulation of uremic toxins, resulting in suppression of red blood cell production and low response to erythropoiesis-stimulating agents 39 , 40 . In addition, spKt/V was negatively correlated with left ventricular mass index and an independent risk factor for Left ventricular hypertrophy 41 . This may be related to the control of volume overload, anemia and hypertension by increasing spKt/V.…”
Section: Discussionmentioning
confidence: 94%